2001
DOI: 10.1046/j.1365-2842.2001.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and solubility of dental composites and identification of monomers released in an aqueous environment

Abstract: Water sorption and solubility of six proprietary composite resin materials were assessed, and monomers eluted from the organic matrix during water storage identified. Water sorption and solubility tests were carried out with the following storage times: 4 h, 24 h and 7, 60 and 180 days. After storage, water sorption and solubility were determined. Eluted monomers were analysed by high performance liquid chromatography (HPLC). Correlation between the retention time of the registered peak and the reference peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
220
2
38

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(272 citation statements)
references
References 35 publications
12
220
2
38
Order By: Relevance
“…The effect of water on VHN of the investigated material can be explained by the difference in the solubility parameter of the water (48.0 ␦/MPa 1/2 ) compared to the resin-based materials. These results were in agreement with other studies comparing different solvents effect on resin-based composites [11,26,37,45,46]. Organic solvents, as Ethanol and MEK, showed more detrimental effect on the mechanical properties compared to water storage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of water on VHN of the investigated material can be explained by the difference in the solubility parameter of the water (48.0 ␦/MPa 1/2 ) compared to the resin-based materials. These results were in agreement with other studies comparing different solvents effect on resin-based composites [11,26,37,45,46]. Organic solvents, as Ethanol and MEK, showed more detrimental effect on the mechanical properties compared to water storage.…”
Section: Discussionsupporting
confidence: 92%
“…Organic solvents, as Ethanol and MEK, showed more detrimental effect on the mechanical properties compared to water storage. Several studies have demonstrated more complete extraction of monomers and oligomers with the organic solvents that could explain their stronger impact on the mechanical properties [8,12,45,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…When the previous factors are standard, behavior will also be affected by the type, rate, and surface area of the filler used, the particular silane treatment, the difference in the monomer structure, and the degree of cross linking. 18 Residual monomers, fillers, degradation products or inhibitors and activators of polymerization are therefore able to leach out from cured resin-based materials. As a result, water sorption and solubility have a significant effect on the clinical success of restorative material, influencing the aesthetic appearance, integrity, and surface properties.…”
Section: Discussionmentioning
confidence: 99%
“…Water sorption and solubility studies have generally revealed that W sp and W sl values change in the same way. 25 Many researchers 16,18,26 have determined that materials with low sorption demonstrate low solubility. Some studies, however, suggest that materials with high water sorption do not necessarily demonstrate high solubility, 27 as shown here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation